STRUCTURAL OPTIMIZATION FOR CONTINUOUS CHANGE RAIL LINE BASED ON IMPROVED ALGORITHMS CHAOS - WU YuanKe; LIU Fang; LIU ChaoQun; LI WenTao; SUN JingKun (Jixie qiangdu)
Summed up six typical working conditions of the rail track replacement device. Its working load is calculated by three kinds of method. And the theoretical model of telescopic rail track replacement car for work equipment is established.Accelerating factor and inertia weight Improved PSO,and adding the chaos algorithm optimize five main parameters of hexagonal cross-section telescopic boom. The optimization results show,telescopic quality has reduced by 29. 6%; overall centroid position has down; counterweight with telescopic functionis smaller; the balance of front and rear axle bogie track replacement has achieved; In other railcars improved machine stability.